Achaemenid Public Government Institutions - Shodmonova Gulizor Farhodovna (Research Parks Publishing LLC, 2020)
Article is devoted to the analysis of Achaemenid methods of governing the state, the history of the empire and institutions of statehood, positions and ranks inthe central state apparatus, the integrated defense system, the tax system, the problems of social and political governance in the Orient.